Small molecule APOL1 inhibitors as a precision medicine approach for APOL1-mediated kidney disease - Brandon Zimmerman; Leslie A. Dakin; Anne Fortier; Evanthia Nanou; Angelo Blasio; James Mann; Howard Miller; Marissa Fletcher; Tiansheng Wang; Suganthini Nanthakumar; Gizelle McCarthy; Caline Matar; et al. (Nature Communications)
Abstract Chronic kidney disease affects ~10% of people worldwide and there are no disease modifying therapeutics that address the underlying cause of any form of kidney disease. Genome wide association studies have identified the G1 and G2 variants in the apolipoprotein L1 (APOL1) gene as major contributors to a subtype of proteinuric kidney disease now referred to as APOL1-mediated kidney disease (AMKD). We hypothesized that inhibition of APOL1 could have therapeutic potential for this genetically-defined form of kidney disease. Here we describe the development of preclinical assays and the discovery of potent and specific APOL1 inhibitors with drug-like properties. We provide evidence that APOL1 channel activity drives podocyte injury and that inhibition of this activity stops APOL1-mediated cell death and kidney damage in a transgenic mouse model. These preclinical data, combined with clinical data from our previously published phase 2 proof-of-concept study, support the potential of APOL1 channel inhibition for the treatment of AMKD.